Formation of students’ knowledge and skills by means of parables and riddles (Multidisciplinary Journal of Science and Technology, 2024)
In this article, mastering the culture of oral speech, knowing its characteristics; to teach the student to compose sentences and speeches in accordance with the standards of the literary language in terms of grammar, orthography, and stylistics. For the development of oral speech, it is necessary to consistently increase the student's vocabulary, to acquire practical knowledge of the syntactic structure of the sentence, to develop skills related to ensuring the logical harmony between speech units, and to connect new letters and sounds. the meaning of the words should be fully understood by the reader. It was thought about working on riddles, proverbs, and wise words